Alternate Cu2 and Er2 spin carriers in a carboxylate bridged chain: EPR study - Calvo, Rafael (2009)
We report powder EPR measurements at 9.48 GHz and temperatures of 4 K e T e 30 K and at 33.86 GHz and T = 300 K for the polymeric compound {[Cu2Er2(L)10(H2O)4] ·3H2O}n (HL ) trans-2-butenoic acid) having alternate Cu2 and Er2 dinuclear units bridged by carboxylates along a chain. Above 70 K, when the ErIII resonance is unobservable and uncoupled from the CuII ions, the spectrum arises from the excited triplet state of antiferromagnetic Cu2 units, decreasing in intensity as T decreases, and disappearing when these units condensate into the singlet ground state. Fit of a model to the spectra at 9.48 and 33.86 GHz and 300 K gives gCu//= 2.379, gCuper = 2.065, DCu= -0.340 cm-1, and ECu ∼ 0 for the g-factors and zero field splitting parameters. From the T dependence of the intensity of the spectrum above 70 K, we obtain JCu-Cu = -336(11) cm-1 for the intradinuclear exchange interaction. Below 50 K, a spectrum attributed to Er2 units appears, narrows, and resolves as T decreases, due to the increase of the spin-lattice relaxation time T1. The spectrum at 4 K allows calculating g values g1=1.489, g2= 2.163, and g3= 5.587 and zero field splitting parameters DEr=-0.237 cm-1 and EEr = 0.020 cm-1. The results are discussed in terms of the properties of the Cu and Er ions, and the crystal structure of the compound.